Separating the Aerosol Effect in Case of a ""Medicane" - Kraut, Isabel (Wissenschaftliche Berichte des Instituts für Meteorologie und Klimaforschung des Karlsruher Instituts für Technologie, 2015)
This work addresses the interactions of aerosols, clouds and dynamics in case of a so-called Medicane. This type of cyclone occurs over the Mediterranean Sea, showing similarities to Hurricanes over the Atlantic and Pacific Ocean. Due to the high wind speed of the Medicane, a large amount of sea salt particles is emitted over the sea. This can influence the development of the Medicane, its associated clouds, and precipitation.